Teacher stress factors in the Metropole North, Circuit 6 of the Western Cape, South Africa - Steenkamp, Peter John (University of Western Cape, 2014)
Magister Educationis - MEd === The aim of this study was to investigate the experiences of stress by teachers in the Metropole North, Circuit 6 of the Western Cape, South Africa, The study investigated factors causing teachers to experience stress as well as the levels or extent of their stress, to determine whether teacher stress due to learners, conditions of service, workload, resources for teaching and school-community relations could explain the variance in total stress experienced by teachers and to determine if there is no statistically significant difference in sources of stress based on the biographical variables (age, gender, marital status and tenure) amongst educators in primary schools.